The evolving core of usable macroeconomics for policymakers - Jonas D. M. Fisher; Bart Hobijn; Alessandro T. Villa (Federal Reserve Bank of Chicago, 2025)
We provide a brief primer on how the core of usable macroeconomic theory for monetary policymakers has evolved over the past 50 years. Today's policy discussions center on the New Keynesian (NK) synthesis, which builds on the Neoclassical growth model and the AS-AD framework. It incorporates nominal and real rigidities, financial and labor market frictions, the importance of expectations, and inspired terms used by policymakers such as "anchored inflation expectations" and "forward guidance." While essential for communication during the Great Recession and COVID-19 pandemic, these events also revealed the NK model's limitations. Newer models incorporating heterogeneous agents potentially offer richer policy insights but add complexity and the challenge of distilling their main policy implications going forward.
Keywords: B22; E50; 330; History of economic thought; monetary policy